UPAYA KEPOLISIAN DALAM MENERAPKAN KEADILAN RESTORATIF TERHADAP KASUS TINDAK PIDANA INFORMASI DAN TRANSAKSI ELEKTRONIK (STUDI DI KEPOLISIAN DAERAH SUMATERA UTARA) - Pinakri, Rapi; Sahari, Alpi (JURNAL DOKTRIN REVIEW, 2023)
ITE crimes are increasingly common in Indonesia, so the National Police Chief issued Circular Number: SE/2/II/2021 concerning Ethical Cultural Awareness to Create a Clean, Healthy and Productive Indonesian Digital Space. The National Police Chief asked National Police Investigators to prioritize restorative justice in resolving cases. The formulation of the problem is how the criminal law perspective applies in implementing restorative justice in ITE criminal cases, and how law enforcement efforts by the North Sumatra Regional Police are implemented in implementing restorative justice in ITE criminal cases, as well as what obstacles North Sumatra Regional Police investigators find in implementing restorative justice in ITE criminal cases. This research method is empirical juridical legal research. In implementing restorative justice in ITE cases, it is regulated in the National Police Chief's Circular Letter No.SE/8/VII/2018, Law enforcement efforts by the Police in implementing restorative justice are carried out namely the preparation, implementation and results stages of Restorative Justice. Obstacles for Police investigators in implementing restorative justice in ITE cases include internal factors including the lack of professionalism of investigators, the ability of the Investigating Organization's resources, and external factors including one of the parties not being willing to make peace, the victim's request to be paid compensation, the perpetrator not being willing to take responsibility. As a suggestion, restorative care should be regulated in law, and restorative efforts should be facilitated by investigators, and investigators should be given special training so that mediation through restorative justice facilities can be carried out well.